La Bible dans les oeuvres des adhérants de l’École des Glossateurs et de l’École des Commentateurs - Hamza, Gábor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
Natural law is the first theory in ethics and philosophy in European legal culture to take a principled interest in the comparison of laws. The following study will examine what tendencies towards comparative law can be discerned in the works of the representatives of natural law in the various periods, and to what extent these were linked to biblical (divine) law. In doing so, the author pays particular attention to the humanist school of law in the Mediterranean, then to the natural law scholars in the 16th-18th centuries, and to some early representatives of the historical school of law, until the cult of Roman law (as ’Kryptonaturrecht’) took the place of the ’defeated’ natural law in the approach of the later representatives of this school. The important links between natural law and comparative law are presented by the author primarily from the point of view of the history of science.